Inhibiting GPIbα Shedding Preserves Post-Transfusion Recovery and Hemostatic Function of Platelets After Prolonged Storage. Issue 9 (September 2016) - Chen, Wenchun; Liang, Xin; Syed, Anum K.; Jessup, Paula; Church, William R.; Ware, Jerry; Josephson, Cassandra D.; Li, Renhao
Abstract : Objective—: The platelet storage lesion accelerates platelet clearance after transfusion, but the underlying molecular mechanism remains elusive. Although inhibiting sheddase activity hampers clearance of platelets with storage lesion, the target platelet protein responsible for ectodomain shedding–induced clearance is not definitively identified. Monoclonal antibody 5G6 was developed recently to bind specifically human platelet receptor glycoprotein (GP)Ibα and inhibit its shedding but not shedding of other receptors. Here, the role of GPIbα shedding in platelet clearance after transfusion was addressed. Approach and Results—: Both human leukoreduced apheresis-derived platelets and transgenic mouse platelets expressing human GPIbα were stored at room temperature in the presence and absence of 5G6 Fab fragment. At various time points, aliquots of stored platelets were analyzed and compared. 5G6 Fab inhibited GPIbα shedding in both platelets during storage and preserved higher level of GPIbα on the platelet surface. Compared with age-matched control platelets, 5G6 Fab–stored platelets exhibited similar levels of platelet activation, degranulation, and agonist-induced aggregation. 5G6 Fab–stored human GPIbα platelets exhibited significantly higher post-transfusion recovery and in vivo hemostatic function in recipient mice than control platelets. Consistently, 5G6 Fab–stored, 8-day-old human platelets produced similar improvement in post-transfusion recovery in immunodeficient mice and in ex vivo thrombus formation over collagen under shear flow. Conclusions—: Specific inhibition of GPIbα shedding in the stored platelets improves post-transfusion platelet recovery and hemostatic function, providing clear evidence for GPIbα shedding as a cause of platelet clearance. These results suggest that specific inhibition of GPIbα shedding may be used to optimize platelet storage conditions. Abstract : Supplemental Digital Content is available in the text.